Edukasi Akad-Akad Syariah Dan Perkembangan Ekonomi Syariah Pada Siswa SMA IT Al Utsaimin - Zakir, Muhammad; Hasda, Mifta; Hidayat, Hidayat; Reza, Saru; Mardiyah, Suci (EL-EMIR INSTITUTE, 2025)
This community service program was carried out for students of SMA IT Al Utsaimin Bangkinang with the main objective of providing education on Islamic contracts (akad-akad syariah) and the development of Islamic economics. This activity is considered important since students’ understanding of the basic concepts of Islamic economics varies, thus requiring systematic efforts through non-formal learning outside the classroom. The methods used in this activity included counseling, presentations, and interactive discussions. The counseling sessions aimed to provide a basic understanding of the principles of Islamic contracts, presentations were used to showcase the development of Islamic economics in Indonesia and globally, while the discussions allowed students to ask questions and clarify their understanding of the material delivered. The results of the activity indicated that the community service program was successfully implemented and carried out in accordance with the planned schedule. In general, students showed great enthusiasm in participating, although their levels of understanding differed. Some students already had a good grasp of Islamic contract concepts, some were still uncertain, and others had not yet fully understood the material. The achievement of the program’s objectives can be considered positive since all activities were successfully conducted with the support of collaboration between the school, the facilitators, and the business owners involved